MEMAHAMI EKUITAS MEREK PERGURUAN TINGGI: PENELITIAN EMPIRIS PADA STIE SURAKARTA, JAWA TENGAH, INDONESIA - Elia Ardyan; Wisnu Sancoyo; Oky Tira Ayuda; Deni Setiadi; Fenti Winda Sari; Atika Ayu Ismawati; Novita Yuniarti; Hafiz Kurniawan; Winata . (Jurnal Manajemen dan Kewirausahaan, 2015)
Measuring brand equity becomes an important part in the organization, especially college. By measuring the brand equity, the college would be more understanding about its brand awareness, brand association, perceived quality, and brand loyalty. The Research problems were: (1) How were the students’ perception about STIE Surakarta brand awareness?(2) How were the effects of brand association and perceived quality on brand loyalty. The samples of this research were 120 students of STIE Surakarta. The analysis used description and Structural Equation Modeling (SEM). The results showed that (1) the brand of STIE Surakarta occupied 3rd position in the minds of consumers; (2) Brand association had positive but insignificant effect on loyalty and perceived quality had positive and significant effect on brand loyalty.